Here's how to treat childhood apraxia of speech - Fish, Margaret A., 1959- (Here's how series., 2016)
"Here's How to Treat Childhood Apraxia of Speech, Second Edition is intended for students, clinicians, and interested parents who work with children with childhood appraxia of speech (CAS) ... The primary focus of this book is to provide practical suggestions for evaluating children with suspected CAS and planning and implementing effective and efficient treatment for children with this complex speech disorder"--Preface